Asunaprevir and daclatasvir for recurrent hepatitis C after liver transplantation: A Japanese multicenter experience. Issue 11 (24th September 2017) - Ikegami, Toru; Ueda, Yoshihide; Akamatsu, Nobuhisa; Ishiyama, Kohei; Goto, Ryoichi; Soyama, Akihiko; Kuramitsu, Kaori; Honda, Masaki; Shinoda, Masahiro; Yoshizumi, Tomoharu; Okajima, Hideaki; Kitagawa, Yuko; et al.
Abstract: The safety and efficacy of an IFN‐free regimen using asunaprevir (ASV) and daclatasvir (DCV) for recurrent hepatitis C virus (HCV) infection after liver transplantation (LT) have not been evaluated in Japan. A multicenter study of LT recipients (n = 74) with recurrent HCV genotype 1b infection treated with ASV‐DCV for 24 weeks was performed. Medical history was positive for pegylated interferon and ribavirin (Peg‐IFN/RBV) in 40 (54.1%) patients, and for simeprevir (SMV) with Peg‐IFN/RBV in 12 (16.2%) patients. Resistance‐associated variants (RAVs) were positive at D168 (n = 1) in the NS3, and at L31 (n = 4), Y93 (n = 4), and L31/Y93 (n = 1) in the NS5A region of the HCV genome. Sixty‐one (82.4%) patients completed the 24‐week treatment protocol. Although sustained viral response (SVR) was achieved in 49 (80.3%) patients, it was achieved in only two (16.7%) patients among those with histories of receiving SMV (n = 12). Univariate analysis showed that a history of SMV ( P < .01) and the presence of mutations in NS5A ( P = .02) were the significant factors for no‐SVR. By excluding the patients with either a history of SMV‐based treatment or RAVs in NS3/NS5A, the SVR rate was 96.4%. By excluding the patients with a history of SMV and those with RAVs in NS3/NS5A, viral clearance of ASV‐DCV was favorable, with a high SVR rate.